Pendampingan Budidaya Udang Vaname Sistem Small Pond di Desa Bades, Lumajang - R. Abdoel Djamali; Mahrus Irsyam; Achmad Subagio; Bambang Piluharto; Indarto Indarto; Agus Dharmawan (Warta LPM, 2023)
Lumajang Regency, especially Bades Village, is one of the central managements of coastal and marine areas in East Java Province. One of the fishermen groups in Bades Village is the Mina Dampar Fishermen Group. Until now, these fishermen groups have not been able to utilize coastal areas for small-scale people's ponds due to limited knowledge of intensive shrimp farming technology, limited access to capital, and limited market information. This Technical Guidance aims to broaden horizons and introduce vannamei shrimp farming technology to fishermen who are members of the Mina Dampar group. This technical guidance activity was carried out at the Fish Landing Base in Bades Village and was targeted at the Mina Dampar Fishermen Group. The mentoring method used is the Participatory Rural Appraisal (PRA) method. This Technical Guidance aims to broaden horizons and introduce vannamei shrimp farming technology to 10 fishermen who are members of the Mina Dampar group. This technical guidance consists of outreach activities and field orientation. This activity shows that fishermen are interested in cultivating vannamei shrimp in Bades Village, especially freshwater vannamei shrimp cultivation. Cultivating freshwater vannamei shrimp can be a source of income for fishermen while doing housework.